Proceedings of the 13th Participatory Design Conference: Short Papers, Industry Cases, Workshop Descriptions, Doctoral Consorti 2014
DOI: 10.1145/2662155.2662194
|View full text |Cite
|
Sign up to set email alerts
|

Participants' view on personal gains and PD process

Abstract: While it is commonly claimed that users of participatory design projects reap benefits from their participation, little research exists that shows if this truly occurs in the real world. In this paper, we introduce the method and results of assessing the participants' perception of their personal benefits and the degree of participation in a large project in the healthcare field. Our research shows that a well-executed participatory design project can produce most of the benefits hypothesized in the literature… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…The study showed that different participants gained in different ways. Expected or anticipated benefits were explored in a study with adults that sought to explore the participants' experience and gains (Garde & Van Der Voort, 2014). In this study questionnaires were used before, during and after the design events to determine changes in the participants' creativity and self-efficacy.…”
Section: Balancing Benefitsmentioning
confidence: 99%
See 2 more Smart Citations
“…The study showed that different participants gained in different ways. Expected or anticipated benefits were explored in a study with adults that sought to explore the participants' experience and gains (Garde & Van Der Voort, 2014). In this study questionnaires were used before, during and after the design events to determine changes in the participants' creativity and self-efficacy.…”
Section: Balancing Benefitsmentioning
confidence: 99%
“…This was followed by another skill rating activity (step 5), and then design (steps 6, 7 and 8 which was stage 4 in Tick Box Design). This was followed by an end evaluation (step 9), that gathered post event impressions (Garde & Van Der Voort, 2014), and a wrap up using PowerPoint (step 10 -stage 5 in Tick Box Design)).…”
Section: Workhop Proceduresmentioning
confidence: 99%
See 1 more Smart Citation
“…One specifc issue is how to equitably and reciprocally "give back" to research participants once the project comes to an end [28,58,72]. While HCI and design researchers agree that plans need to be envisioned for what happens when a research project is completed and they "leave the feld" (e.g., [32,41,67,70]), it still is a recurring challenge on how exactly such strategies can be feasibly enacted. Additionally, translating theoretical or empirical knowledge derived from HCI research into a form that can positively engage both the people that participated in the research itself and the general population alike, can be slow, unpredictable, and incongruent (e.g., [10,16,56]).…”
Section: Introductionmentioning
confidence: 99%
“…One of the fundamental principles in PD is the importance of mutual learning and the development of shared understandings between designers and other participants [25]. However, the personal benefits that participants can gain from PD are relatively unexplored [8,14]. McNally et al investigated the sustained benefits for children in participatory design projects [18], Schepers et al distilled user gains for vulnerable children in a long-term project [26], Börjesson et al investigated teachers gains from PD activities [7].…”
Section: Introductionmentioning
confidence: 99%